Effect of sodium hydroxide and formic acid treatments on charpy impact and tensile strength properties of ready-made garment, waste reinforced polyester composites - (:unkn) unknown (Fiber Society, 2014)
In this study ready-made garment waste cotton fiber were treated with NaOH and acetic acid then mixed with ready-made garment waste polypropylene fibers then polymer composites were produced from these treated cotton/polypropylene blend by using thermoset polyester resin as matrix. Tensile strength and charpy impact strength properties of treated waste cotton/polypropylene fiber blends reinforced thermoset polyester composites were investigated.
Keywords: Composite; Polyester resin; Polypropylene; Surface treatment; Textile waste